Suspected anthrax outbreak: Investigation in a rural block of west Bengal and public health response - Tushar Kanti Mondal; Somenath Ghosh; Samir Dasgupta; Aditya Prasad Sarkar (Wolters Kluwer Medknow Publications, 2015)
Anthrax is one of the top 10 diseases reported in India and also one of the major causes of death in livestock. This study was conducted to confirm the outbreak of suspected anthrax, determine the transmission mechanism, and implement control measures in Bhatar block of Burdwan district, West Bengal, India. A cross-sectional descriptive study was conducted through house-to-house visits in Oregram and Kathaldanga villages during the period from May 30, 2013 to June 8, 2013. Out of the 93 persons exposed to anthrax, 11 persons had history of slaughtering, while 82 consumed the meat. All of the 7 cases of suspected anthrax were male (mean age 41.14 ± 10.04 years) and involved in slaughtering the animal. Most cases presented with papule and vesicle over the upper extremity and the trunk. One patient among the suspected cases died. The outbreak was labeled as a suspected anthrax outbreak. A health awareness camp was organized to improve awareness of anthrax among villagers.